The stability of information cascades: how herd behavior breaks down - Hans Mewis (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1998)
We extend the standard model of information cascades to situations where agents have to choose between switching to a new alternative or not. In particular, we add two new features to the standard model. First, agents continue to receive signals after they have chosen 'switching'; and second agents may revert their earlier decisions. The focus of the paper is to analyze how information is passed on within an information cascade, and the conditions under which breakdown occurs. We identify rules which describe the learning process and run simulations to estimate the properties of the information cascade. – – Wir erweitern das Standardmodel der Informationskaskade. Durch die Erweiterung lassen sich Situationen modellieren, die den Individuen die Wahl zwischen einer neuen Alternative und dem bewährten lassen. Die Erweiterung besteht aus zwei Aspekten. Erstens erhalten die Individuen weiterhin Signale, nachdem sie sich für die neue Alternative entschieden haben. Zweitens können sie ihre Entscheidung später wieder zurücknehmen. Wir untersuchen wie sich Information innerhalb der Informationskaskade ausbreitet und unter welchen Bedingungen die Informationskaskade abbricht. Wir beschreiben den Lernprozeß der Individuen und führen eine Simulation des Prozesses durch.
Keywords: 330